Phthalates and organophosphates in settled dust and HVAC filter dust of U.S. low-income homes: Association with season, building characteristics, and childhood asthma. (December 2018) - Bi, Chenyang; Maestre, Juan P.; Li, Hongwan; Zhang, Ge; Givehchi, Raheleh; Mahdavi, Alireza; Kinney, Kerry A.; Siegel, Jeffrey; Horner, Sharon D.; Xu, Ying
Abstract: Phthalates and organophosphates are ubiquitous indoor semi-volatile organic contaminants (SVOCs) that have been widely used as plasticizers and flame retardants in consumer products. Although many studies have assessed their levels in house dust, only a few used dust samples captured by filters of building heating, ventilation, and air conditioning (HVAC) systems. HVAC filters collect particles from large volumes of air over a long period of time (potentially known) and thus provide a spatially and temporally integrated concentration. This study measured concentrations of phthalates and organophosphates in HVAC filter dust and settled floor dust collected from low-income homes in Texas, United States, in both the summer and winter seasons. The most frequently detected compounds were benzyl butyl phthalate (BBzP), di-(2-ethylhexyl) phthalate (DEHP), di-n-octyl phthalate (DnOP), tris (1-chloro-2-propyl) phosphate (TCIPP), triphenyl phosphate (TPHP), and tris (1, 3-dichloroisopropyl) phosphate (TDCIPP). The median level of TCIPP in settled dust was 3- to 180-times higher than levels reported in other studies of residential homes. Significantly higher concentrations were observed in HVAC filter dust as compared to settled dust for most of the frequently detected compounds in both seasons, except for several phthalates in the winter. SVOC concentrations in settled dust in winter were generally higher than in summer, while different seasonality patterns were found for HVAC filter dust. Settled dust samples from homes with vinyl flooring contained significantly higher levels of BBzP and DEHP as compared to homes with other types of floor material. The concentration of DEHP and TDCIPP in settled dust also significantly associated with the presence of carpet in homes. Cleaning activities to remove dust from furniture actually increased the levels of certain compounds in HVAC filter dust, while frequent vacuuming of carpet helped to decrease the concentrations of some compounds in settled dust. Additionally, the size and age of a given house also correlated with the levels of some pollutants in dust. A statistically significant association between DEHP concentration in HVAC filter dust in summer and the severity of asthma in children was observed. These results suggest that HVAC filter dust represents a useful sampling medium to monitor indoor SVOC concentrations with high sensitivity; in contrast, when using settled dust, in addition to consideration of seasonal influences, it is critical to know the sampling location because the type and level of SVOCs may be related to local materials used there. Highlights: Phthalates and organophosphates were detected in HVAC filter dust and settled dust of U.S. low-income homes Significantly higher SVOC concentrations in HVAC filter dust than in settled dust were observed Different seasonality patterns were found between SVOC concentrations in settled dust and in HVAC filter dust Significant associations between SVOC concentrations in dust and building characteristics were observed Severity of asthma in children was significantly associated with DEHP concentration in HVAC filter dust in summer